Finite Difference Computing with Exponential Decay Models - Langtangen, Hans Petter (Lecture Notes in Computational Science and Engineering,, 2016)
This text provides a very simple, initial introduction to the complete scientific computing pipeline: models, discretization, algorithms, programming, verification, and visualization. The pedagogical strategy is to use one case study - an ordinary differential equation describing exponential decay processes - to illustrate fundamental concepts in mathematics and computer science. The book is easy to read and only requires a command of one-variable calculus and some very basic knowledge about computer programming. Contrary to similar texts on numerical methods and programming, this text has a much stronger focus on implementation and teaches testing and software engineering in particular. .